Analysis of the relationship between teacher-student communicative didactic interactions and meaningful learning in the phonetics l course - Sulca Alarcón, Carmen Pamela (2024)
This study examines the relationship between teacher-student didactic interaction and meaningful learning in the Fonética I course. A quantitative approach with a correlational design and complementary descriptive analysis was applied. The instruments used included a Likert-scale survey to assess didactic interaction (completed by both students and the teacher) and a survey and a knowledge test that assessed the dimensions of meaningful learning (attitudinal, procedural, and conceptual), completed solely by the students. Results showed a positive and significant relationship between didactic interaction and meaningful learning in the attitudinal and procedural dimensions. However, no significant relationship was found between didactic interaction and meaningful learning in the conceptual dimension. The findings conclude that didactic interaction is key to meaningful learning, particularly when it fosters active student participation. External factors such as virtual learning environments and lack of technological resources negatively affect these interactions. Recommendations include strengthening didactic strategies, improving access to technological resources, and training teachers in innovative methodologies to enhance educational quality.